De bijdrage van de techniekgeschiedenis aan de geschiedenis van Nederland. Een reactie op Karel Davids, Pim Kooij en Geert Vanpaemel - Schot, J.; Lintsen, H.; Rip, A.; Albert de la Bruhèze, A. (BMGN - Low Countries Historical Review, 2005)
The History of Technology’s contribution to the history of the Netherlands. A response to remarks made by Karel Davids, Pim Kooij and Geert Vanpaemel The editors welcome the point emphasised in the reviews that the history of technology adds an extra dimension to the history of the Netherlands. The added value of the series is that it demonstrates how choises were made by different groups on the structure of society through the design of technological developments. Significantly, certain choices in the twentieth century were not discussed. Almost all the stakeholders in society opted for modernisation. The only thing they discussed was the route they should take to get there. The series therefore presents a history that emphasises human agency, albeit within the confines of changing circumstances. The comments highlight areas where further fruitful cooperation among historians is possible. For example, themes such as the implementation of government policies and the power of engineers (democracy versus technocracy), and the relationship between a pillarised middlefield and a non-pillarised one. One important issue linked to new research is wether or not the framework of the nation-state should be so dominant. This response is part of the discussion forum ’Techniek in Nederland in de twintigste eeuw’ (J. Schot, H. Lintsen, A. Rip, A. Albert de la Bruhèze).